Accuracy, Interpretability, and Differential Privacy via Explainable Boosting - Nori, Harsha; Caruana, Rich; Bu, Zhiqi; Shen, Judy Hanwen; Kulkarni, Janardhan (Jana) (2021 International Conference on Machine Learning, 2021)
We show that adding differential privacy to Explainable Boosting Machines (EBMs), a recent method for training interpretable ML models, yields state-of-the-art accuracy while protecting privacy. Our experiments on multiple classification and regression datasets show that DP-EBM models suffer surprisingly little accuracy loss even with strong differential privacy guarantees. In addition to high accuracy, two other benefits of applying DP to EBMs are: a) trained models provide exact global and local interpretability, which is often important in settings where differential privacy is needed; and b) the models can be edited after training without loss of privacy to correct errors which DP noise may have introduced.